Stoichiometry-driven heuristic feedforward control for oxygen supply in a biological gas desulfurization process. (October 2020) - Kiragosyan, Karine; Roman, Pawel; Keesman, Karel J.; Janssen, Albert J.H.; Klok, Johannes B.M.
Abstract: In this work, a stoichiometry-driven heuristic feedforward control strategy is proposed for controlling the oxygen supply to a biological gas desulfurization process that treats biogas, landfill, and high-pressure natural gas containing H2 S and volatile organic sulfur compounds (VOSC). Traditionally, PI or PID feedback control is used when the feed gas contains H 2 S only. Because the oxidation–reduction potential (ORP) is mostly dominated by the dissolved sulfide concentration, the feedback controller maintains a constant sulfide concentration in the bioreactor by maintaining an ORP setpoint value through controlling the oxygen supply. However, when the feed gas also contains VOSCs, e.g., thiols, it appears from our research that controlling ORP at a fixed value does not lead to stable process performance. Hence, an alternative control strategy is proposed, which controls the O 2 /H 2 S supply ratio based on the stoichiometry of the dominant chemical reaction and experimental experience. The heuristic feedforward control strategy was validated by a fluctuating supply of H 2 S (26.5 to 126.5 mM S day −1 ) in the absence and presence of ethanethiol (0.8 to 1.16 mM S day −1 ). A sulfur selectivity above 95 mol%, and complete removal of H 2 S, was achieved at an O 2 /H 2 S supply ratio of about 0.63 mol mol −1 compared to 56 mol% when a PI/PID controller was used at a randomly varying, stepwise H2 S dosing rate This work shows that fluctuations in the H 2 S loading rate and presence of ethanethiol in the feed gas of full-scale systems can be controlled by applying the heuristic feedforward control strategy. However, online measurements of the H2 S concentration in the feed gas are required to implement the proposed strategy in full-scale installations successfully. Highlights: Feedforward control strategy is based on O2 /H2 S supply mol ratio. Oxygen supply is more stable with use of the feedforward control strategy. Sulfur formation is enhanced with use of feedforward control strategy. O2 /H2 S ratio-based control shows good results in the presence of thiols.